(untitled) (Carte Romanze, 2023)
Berlin and Kay’s theory on the use of color in human societies (which really concerns the linguistic terms with which such colors are perceived and defined) and Michel Pastoureau’s research are important for the study of the functioning of cultures in time and space.The article aims to examine the use of color – a particular colour, the white – in a text that belongs to the European Middle Ages, the romance entitled «Les Merveilles de Rigomer», composed towards the end of the 13th century in an area of North-Eastern France, focusing on the character of the knight Lancelot, the figure on which the meaning of the romance is structured and organized.